Dynamic behaviour of axially-loaded RC columns under horizontal impact loading. (1st August 2018) - Cai, Jian; Ye, Jia-Bin; Chen, Qing-Jun; Liu, Xinpei; Wang, Yong-Qi
Highlights: Tests on axially-loaded RC columns under horizontal impact loading are addressed. Modern horizontal impact test facility is adopted. Experimental tests are described with detailed results being given. Comparison of impact force responses under horizontal and drop weight impact loads. Comparison between test results and predictions by empirical formulations. Abstract: This paper presents an experimental study undertaken for investigating the dynamic responses of axially-loaded reinforced concrete (RC) columns under horizontal impact loading. A total of 15 square RC columns, categorised by three different types of cross-section dimensions, were tested using horizontal impact facilities. The test specimens had fixed boundary condition at their bottoms. The impact load was realised by a test truck and applied at the top position of the RC column. Three main parameters, namely the slenderness ratio, the impact weight and the impact velocity, are considered in the study. Based on the experimental results, the crack pattern, impact force, deformation, strain development and energy dissipation are discussed. Through the recording of the relative movement between hammer and specimen, the repeated process of contact and separation was observed. Compared with that of the conventional drop weight impact test, the impact force-time history curves obtained from the horizontal impact test show more fluctuation at the stabilisation stage, because the existence of gravitational acceleration of drop hammer and larger velocity in drop weight impact test accelerates the repeated process of contact and separation between the hammer and specimen. As the input impact energy increases, the flexure-controlled failure of column was observed, which is characterised by the yielding of tensile reinforcement and the spalling of concrete cover. The experimental results presented herein provide benchmark data for the further research study of RC columns subjected to horizontal impact forces. The equivalent static force calculated by empirical formula of AASHTO is adopted to compare with the experimental results, which indicates that the empirical equation only related to the impact weight and velocity could overestimate the equivalent static force that would leads to too conservative impact-resistance structural design.